Mass- and Energy-Balance Modeling and Sublimation Losses on Dokriani Bamak and Chhota Shigri Glaciers in Himalaya Since 1979 - Srivastava, Smriti; Azam, Mohd. Farooq (Frontiers in Water, 2022)
Available surface energy balance (SEB) studies in the Himalaya, generally, investigate the melt-governing energy fluxes at a point scale. Further, the annual glacier-wide mass balance (Ba) reconstructions have often been performed using temperature-index (T-index) models. In the present study, a mass-, and energy-balance model is used to simulate the Ba on Dokriani Bamak Glacier (DBG, central Himalaya) and Chhota Shigri Glacier (CSG, western Himalaya) using bias-corrected ERA5 data over 1979-2020. The model is calibrated using in-situ Ba and validated against available in-situ altitudinal and geodetic mass balances. DBG and CSG show mean Ba of –0.27 ± 0.32 and –0.31 ± 0.38 m w.e. a−1 (meter water equivalent per year), respectively over 1979-2020. Glacier-wide net shortwave radiation dominates the SEB followed by longwave net radiation, latent heat flux and sensible heat flux. The losses through sublimation are around 22% on DBG and 20% on CSG to the total ablation with a strong spatial and temporal variability. Modelled Ba is highly sensitive to snow albedo —with sensitivities of 0.29 and 0.37 m w.e. a−1 for 10% change in calibrated value— on DBG and CSG, respectively. The sensitivity of modelled mean Ba to 1oC change in air temperature and 10% change in precipitation, respectively is higher on DBG (–0.50 m w.e. a−1 oC-1, 0.23 m w.e. a−1) than CSG (–0.30 m w.e. a−1 oC-1, 0.13 m w.e. a−1). This study provides insights into the regional variations in mass-wastage governing SEB fluxes at glacier-wide scale, which is helpful for understanding the glacier-climate interactions in the Himalaya, and stresses an inclusion of sublimation scheme in T-index models.